Role of diagnostic hysterolaparoscopy in the evaluation of female infertility - N., Madhuri; S., Rashmi H.; S., Sujatha M.; G., Dhanyata (International Journal of Research in Medical Sciences, 2019)
Background: Infertility is defined by WHO as a disease of the reproductive system defined by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. The prevalence of infertility is about 10%-15% of reproductive age couples. Female factor is responsible for 40-45% of etiology of infertility. Aim of the study was to evaluate the role of diagnostic hysterolaparoscopy in female infertility at a tertiary care centre. Methods: This is a retrospective hospital based study done at a tertiary care hospital attached to JSS Medical College, Mysuru between January 2017 and December 2018. Infertile women with primary or secondary infertility in the 18-40 years age group, with normal hormonal profile and no known male factor were included. Results: In our study, primary infertility was found in 77% of the 96 patients and secondary infertility was found in 23% of patients. In primary infertility, ovarian pathology was the most common finding while Endometriosis was the most common finding in secondary infertility group. 77 % patients were found to have bilaterally patent tubes while remaining had unilateral or bilateral blockage. On hysteroscopy, endometrial polyps were the commonest hysteroscopic finding in both groups. Conclusions: Combined hystero-laparoscopy is a safe, effective and reliable method in comprehensive evaluation of infertility. It helps in the diagnosis of pelvic pathology which may have been missed by routine examination and thereby helps in optimal management of female infertility.